Modal Logic as a Methodological Tool in Epistemology: Notes for (another) possible overcoming of skeptical arguments - Fernández Cuesta, José Alejandro (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In this paper we intend to offer a first approach to the incorporation of certain formal tools in the elucidation of some issues discussed in epistemological contexts. The aim is not to offer an exhaustive resolution of these problems but merely to point out the usefulness of modal semantics when applied to different fields. Here we will show how a series of skeptical arguments eventually involve a modal (counterfactual) structure, which we will try to generalise into a useful scheme.